Pediatric unit spending in the North of Italy during the COVID-19 pandemic - Roberto Franceschi; Evelina Maines; Angelamaria Petrone; Simone Bilato; Ilaria Trentini; Lorenzo Di Spazio; Luca Leonardi; Massimo Soffiati; Andrea Francesconi (BMC, 2023)
Abstract Background During the COVID-19 pandemic, accesses to pediatric health care services decreased, as well as the consumption of traditional drugs, while the median cost per patient at the emergency department slightly increased and the cost of pediatric COVID-19 admissions to the pediatric ward too. Overall spending of a secondary level Pediatric Unit in the last two years has not been previously reported. Methods This is a retrospective study conducted by the Pediatric Unit of S. Chiara Hospital of Trento, North of Italy. We collected data on consumption and spending before and during the COVID-19 pandemic (between January 2018 and December 2022). Results The total spending ranged from 2.141.220 to 2.483.931 euros between 2018 and 2022. COVID-19 spending accounted only for 5-8% of the overall budget, while two macro-areas of spending were identified: (i) biologic drugs for inherited metabolic diseases (IMDs), that impacted for 35.4-41.3%, and (ii) technology devices for type 1 diabetes (T1D), that accounted for 41.6-32.8% of the overall budget, in 2021 and 2022, respectively. Analysis of costs along with the different health care services revealed that: (i) the spending for COVID-19 antigen tests and personal protective equipment had a major impact on the Emergency room budget (from 54 to 68% in the two years); (ii) biological drugs accounted mainly on the Pediatric Ward (for 57%), Day Hospital (for 74%) and rare disease center budget (for 95% of the spending); (iii) the cost for T1D devices was mainly due to continuous glucose monitoring, and impacted for the 97% of the outpatient clinic budget. Conclusions The main impact on the budget was not due to COVID-19 pandemic related costs, but to the costs for biologic drugs and T1D devices. Therefore, cost savings could be mainly achieved through generic and biosimilars introduction and with inter-regionals calls for technology devices. We emphasize how the control of spending in pediatric hospital care has probably moved from the bedside (savings on traditional drugs as antibiotics) to the bench of national or inter-regional round tables, to obtain discounts on the costs of biologic drugs and medical devices. Here we provide for the first-time in literature, data for bench-marking between secondary level Pediatric Units before and during the COVID-19 pandemic.